BUDAYA ORGANISASI MEMODERASI PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI BERPRESTASI TERHADAP KINERJA GURU - 11.52.02.0129, Johny B Horsman (Jurnal Mahasiswa Pasca Sarjana, 2013)
In this study, the authors focused on the influence of organizational culture, transformational leadership, Achievement Motivation Against Teacher Performance. In addition, this study also conducted to determine the organizational culture as a variable moderate Leadership Transformasioanal and Achievement Motivation on teacher performance in SMP Negeri 04 Sub Rayon 04 Semarang. Total population in this study was 183 teachers, while the number of samples is 107 teachers. Data collection methods used in this study is the method of questionnaire with Likert scale 1-5. Furthermore, the author uses primary data obtained from respondents answers to aquestionnaire. Data processing using statistical techniques, multiple linear regression analysis to analyze the data.The results showed that the Organizational Culture and Leadership Transformasioanal. simultaneously contribute to teacher performance as much as 38%. Moderate Achievement Motivation does not affect the performance of teachers. Achievement motivation was not significant with a significance of 0.420 is greater than 0.05. Organizational culture has a more dominant effect on teacher performance. Achievement motivation did not affect the performance of teachers, and the culture of the organization does not moderate Transformasioanal Ledership and Achievement Motivation Leadership on Teacher Performance. Keywords: transformasioanal leadership, achievement motivation, organizational culture, and performance of teachers